FORMATION OF POSITIONS OF PROSECUTORS IN PRE-REVOLUTIONARY RUSSIA - GOLOVKO I.I. (Legal Bulletin)
Relevance. Emperor Peter I created the post of Prosecutor General, the posts of chief prosecutors in the Senate and Synod, prosecutors in collegiums and courts. The Chief Prosecutor was not connected with other prosecutors, except for the Prosecutor General, to whom he was subordinate. All subordinate prosecutors were subordinate to the Prosecutor General, who was subordinate to the Emperor. The main goal. The article is devoted to the disclosure of the features of the creation of the system of posts of prosecutors in Russia before of 1917, reflected in the legislative provisions. The problems under consideration. The path of historical development was accompanied by the creation and liquidation of the posts of prosecutors, the transformation of the structure of their subordination. As a significant negative result of the formation of the posts of prosecutors and the Judicial Reform of 1864, the abolition of the posts of provincial prosecutors is considered. Formed as a result of the Judicial Reform of 1864, the structure of the posts of prosecutors in terms of judicial supervision was the most developed, the hierarchy was maintained with the subordination of all subordinate prosecutors to the Prosecutor General. However, the following circumstances prevent the definition of this structure as a system with signs of integrity and independence: the continued isolation of the position of the chief prosecutor, the combination of the Prosecutor General of the position of the Minister of Justice. Methods used: within the framework of a systematic approach, the dialectical method of research, methods of analysis and synthesis are applied.